Model Relasi Agama dan Negara dalam Konteks Keindonesiaan: Telaah Pemikiran Nurcholish Madjid dan Abdurrahman Wahid - Milawati, Milawati; Rijal, Tabhan Syamsu; Santalia, Indo (FASTABIQ: JURNAL STUDI ISLAM, 2025)
This study aims to explore models of the relationship between religion and the state in the Indonesian context by examining the thoughts of two prominent moderate Muslim intellectuals: Nurcholish Madjid and Abdurrahman Wahid. Utilizing a qualitative method through library research and content analysis, this study analyzes academic literature, ideological interpretations, and the socio-political historical context of Indonesia. The findings reveal three prevailing approaches: the integralistic, the secularistic, and the ethical-substantive model. Both Madjid and Wahid advocate for the ethical-substantive approach, which promotes justice, freedom, and deliberation within a democratic framework, without turning religion into a state ideology. The study concludes that their moderate perspectives are highly relevant for maintaining a balance between religious spirituality and state rationality in a pluralistic society. It is recommended that this ethical-substantive approach be adopted in public policy formulation and inclusive civic education in Indonesia.Keywords: Religion; State; Democracy; Ethical-Substantive Approach; Indonesia.